Role of Principal Leadership Engagement, Organizational Climate, Job Satisfaction on Teacher Organizational Commitment - Munte, Risma Nurhaini; Siagian, Ester Mawar; Sihombing, Delviana RW; Susanti, Desi (Fakultas Ekonomi, Universitas Negeri Semarang, 2022)
This research aimed to analyze the effect of principal leadership, organizational climate, and job satisfaction on teacher organizational commitment at the private high school level in Pematangsiantar City, Indonesia. This research used a research design oriented to an associative quantitative approach. Data collection techniques in this study used documentation instruments and online questionnaires. The number of samples was 110 respondents. The sampling technique used a non-probability sampling approach using the purposive sampling formula. This research explained that principal leadership, organizational climate, and job satisfaction had a positive and significant effect on teacher organizational commitment. This study confirmed that the implementation of relational principal leadership and changing strategy into practice could increase work commitment of teachers at the school organizational level. In addition, the results of this research also confirmed that the organizational climate of each school had been going well and the job satisfaction of the majority of teachers had met the standards with what they expected with a reflection of satisfaction with the work they did and the satisfaction of co-workers had met expectations.